Challenges and Opportunities With On-Farm Research: Total and Soluble Reactive Stream Phosphorus Before and After Implementation of a Cattle-Exclusion, Riparian Buffer - Georgakakos, Christine B.; Morris, Chelsea K.; Walter, M. Todd (Frontiers in Environmental Science, 2018)
Many nutrient mitigation best management practices (BMP) are promoted by state and federal agencies to protect water quality from animal agriculture. The measured effectiveness of these is highly variable in the research literature. Here, we establish pre- and post-BMP monitoring to evaluate the effectiveness of fencing out cattle from the riparian zone on water quality, specifically, phosphorus (P) loads and concentrations. We collected water samples year-round both before and after a cattle exclusion was established at a small mixed dairy and beef cattle pasture where cattle have historically grazed with unrestricted access to first and second order streams, and analyzed for soluble reactive and total P. Immediately after fence construction, we observed a significant reduction in total P in the stream but not in soluble reactive P. We also observed the development of new runoff source areas and short-circuiting of the riparian buffer as well as repeated presence of cows in the fenced-out area, all of which may diminish the potential effectiveness of this practice. Because BMPs will perform uniquely given climate and landscape position and how managers maintain them, we suggest the need for more nuanced guidance for future BMP designs to ensure successful outcomes.